Custo social das incapacidades por acidentes de trânsito em Fortaleza - Pordeus, Augediva Mana Jucá (2004)
Dísabilities because of traffic accidents and their consequences on people’s life, are a little known issue. Beginning on the assumption that social costs of these dísabilities are high, an attempt was made to evaluate them. A transverse cut study was made on 16 rehabilitation clinics, eight belonging to the SUS Net and eight private, located ín 12 neighborhoods of Fortaleza, on which, in a three month period, a data gathering form was applied on 221 victims of traffic accidents, who were undergoing physiotherapy. It was verified, that young male adults, married or in an informal union, with an income between one and three minimal salaries, where the most frequently assisted ones, on the clinics under study, and among those ones, the more noticeable, were pedestrians and bicycle drivers, by number of cases. About one third received pre-hospitalary assistance by a specialized team. 81.4% of victims under study where hospitalized, by an average time of 24.2 days for patients of clinics belonging to the SUS Net and 10.2 days for private clinics. Direct social costs, distínguished by expenses with diagnostics, treatment and rehabilitation, where high. The cost of pre-hospital assistance was estimated as R$ 34,048.00, while that of hospital assistance was as well estimated as about R$ 8,565,840.00 , and of R$ 26,445.00 for those who received emergency assistance. 86.7% of victims undergoing hospitalization were submitted to surgery, and 79.5% of these had a prosthesis implanted. Hospitalization was statistically significant for emergency aid received from a specialized team (p < 0,001). Besides prosthesis, 78.2% used orthesis. Up to the moment of data gathering, people under study had already received an average of 8.2 medicai consults, taking part of 41 sessions of physiotherapy and 64 of labour therapy. The cost of that assistance, for patients of both assistance systems, was an average of R$ 56,475.28. The chance of participants who were hospitalized, to remain under physiotherapic treatment, for a time > 15 days was 2.25 times higher (confidence interval95% 1.28 to 3.96). Indirect social costs were also high; after the accident, 97.3% said to have temporary restriction for daily activities and 43,9% admitted they had remained with some permanent restriction. The mean restriction time was 136 days. About 83% of victims remained without working or studying and, at the moment of data gathering, 60.2% were still not working or studying. Financial impact on person and family from the accident was considered as big by about 33% of victims, and for the remaining 67.0% it was regular, little, or there wasn’t any at all. The majority of them, 92.3%, needed personal assistance after the accident, and that need interfered respectively in 27.1% and 31.2% on the relationship and dynamics of their families. Difficulties to take part of social activities were claimed by 45.7% as very high, regular and little by about 24.0%; while 30.3% said didn’t have any difficulty at all. The results obtained, showed proximity with information about social costs of traffic accidents being high; a reality was unveiled, which was unknown before in the universe under research. The knowledge produced on dísabilities because of traffic accidents, shall be put through in public policies aiming prevention, and promotion of health. Implantation is herein proposed, of an epidemiological surveillance system on accidents and violence in the rehabilitation clinics of Fortaleza, for the watch of these damages to be made possible.